1993
DOI: 10.1111/j.1365-2621.1993.tb06127.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Minimally Processed Apple Slices from Selected Cultivars

Abstract: Twelve cultivars were prepared as slices and stored 12 days at 2°C. Changes in respiration and quality factors were compared. Initial respiration rates among cultivars varied from 3.5 mL CO&g/hr in Delicious to 7.6 mL CO&$hr in Monroe and decreased rapidly during the first 3 days. Idared, McIntosh, Delicious, and Rome showed relatively low respiration throughout storage. Firmness of slices during storage decreased gradually for 7 days and more rapidly thereafter. Empire, Golden Delicious, and Idared apples sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 7 publications
4
44
0
1
Order By: Relevance
“…No significant difference in the concentration of soluble solids among all studied treatments and the control was observed during 14 days of storage (p > 0.05), which is similar to the result reported by Rocha and Morais (2003). Kim, Smith, and Lee (1993) also reported no changes in the soluble solids content of several apple cultivars during storage.…”
Section: Titratable Acidity and Soluble Solidsmentioning
confidence: 92%
“…No significant difference in the concentration of soluble solids among all studied treatments and the control was observed during 14 days of storage (p > 0.05), which is similar to the result reported by Rocha and Morais (2003). Kim, Smith, and Lee (1993) also reported no changes in the soluble solids content of several apple cultivars during storage.…”
Section: Titratable Acidity and Soluble Solidsmentioning
confidence: 92%
“…Kim et al 17 reported that colour changes of 12 apple cultivars showed a rapid decrease in L * values and they assumed that changes were due to enzymatic browning caused by tissue damage with consequent enhanced contact between enzymes and substrates.…”
Section: Changes In Colour Values During Dehydrationmentioning
confidence: 99%
“…The respiration rates were 1.94, 1.30 and 0.53 mL/(kg.h) CO 2 at 8, 4 and 1 °C, respectively. Since the respiration rate of seeds is important in storage life of minimally processed products, the respiration rate is an important criterion for temperature selection and should be minimal (11). Thus, storage temperature at 1 °C was selected as the best for keeping quality.…”
Section: Effect Of Storage Temperaturementioning
confidence: 99%